Kedudukan Mahkamah Konstitusi Dalam Sistem Hukum Ketatanegaraan Indonesia - Felicia Felicia (Publikasi Indonesia, 2022)
In the Indonesian constitutional law system, it is known as the Constitutional Court, which is a high state institution which is the holder of judicial power together with the Supreme Court. It can be said there are two actors of judicial power, namely the Constitutional Court and the Supreme Court. The problem in this article is what is the position and authority of the Constitutional Court in the Indonesian constitutional law system. The Constitutional Court here has an equal and high position with the Supreme Court, which means that no one has a position below it. The authority of the Constituional Court is regulated in Article 24C paragraph (1) of the 1945 Constitution, among others, to decide on the dissolution of political parties, to give a decision on the opinion of the House of Representatives that the President and Vice President because they have violated the law in the form of bribery, betrayal of the state, commit corruption, other serious crimes or disgraceful acts, examine laws against the 1945 Constitution, decide disputes regarding election results, and decide on disputes over the authority of state institutions whose authority is granted by the 1945 Constitution.